Photoprotective responses of Mediterranean and Atlantic trees to the extreme heat-wave of summer 2003 in Southwestern Europe - García-Plazaola, José Ignacio; Esteban, Raquel; Hormaetxe, Koldobika; Fernández-Marín, Beatriz; Becerril, José Maria (Trees, 2008)
Summer 2003 was extremely hot in Europe. High light in combination with heat and drought exacerbates the generation of photo-oxidative stress. Under these conditions photoprotective responses can be critical for plant survival. Photoprotection was analysed in 2003 in several Mediterranean and Atlantic woody species. These data were compared with previous summers (1998, 1999 and 2001) to evaluate the potential acclimation for each species. A pattern of changes consisting on a decrease in chlorophyll, ascorbate and Fv/Fm and an increase in tocopherol, xanthophyll cycle pigments (VAZ) and deepoxidation index was regularly observed. Acclimation potential was measured by the use of the plasticity index for each parameter. Mediterranean species were more plastic than Atlantic ones. The latter were unable to increase antioxidant pools to the same extent or to downregulate the efﬁciency of light energy conversion. These results indicate that most Mediterranean species are able to perform an efﬁcient acclimation to heat stress, whilst Atlantic species will be more affected by climate warming.
Keywords: á summer 2003; antioxidants; antioxidants á heat-wave á; heat-wave; mediterranean species; mediterranean species á photoprotection; photoprotection; summer 2003

Photoprotective responses of Mediterranean and Atlantic trees to the extreme heat-wave of summer 2003 in Southwestern Europe (Trees, 2008)
Summer 2003 was extremely hot in Europe. High light in combination with heat and drought exacerbates the generation of photo-oxidative stress. Under these conditions photoprotective responses can be critical for plant survival. Photoprotection was analysed in 2003 in several Mediterranean and Atlantic woody species. These data were compared with previous summers (1998, 1999 and 2001) to evaluate the potential acclimation for each species. A pattern of changes consisting on a decrease in chlorophyll, ascorbate and Fv/Fm and an increase in tocopherol, xanthophyll cycle pigments (VAZ) and deepoxidation index was regularly observed. Acclimation potential was measured by the use of the plasticity index for each parameter. Mediterranean species were more plastic than Atlantic ones. The latter were unable to increase antioxidant pools to the same extent or to downregulate the efﬁciency of light energy conversion. These results indicate that most Mediterranean species are able to perform an efﬁcient acclimation to heat stress, whilst Atlantic species will be more affected by climate warming.